Plant Based Naturel Dyes and Wool Yarn Applications - TÜM CEBECİ, DİLEK (My University, 2024)
Plant based natural dyeing is a dyeing process obtained from the dyes of variousplants. These dyestuffs are generally obtained from different structures of plants suchas roots, stems, leaves, flowers, branches, underground shoots. Natural dyeing is theprocess of applying recipes that have been used traditionally from past to presentwithin the framework of certain methods. As one of the richest regions in the world interms of plant diversity, natural dyestuffs have been produced in many regions ofAnatolia for centuries and have been used especially in the textile field. Thesedyestuffs are also of great importance in the weaving culture, which is among thetraditional handicrafts. Especially in recent years, with the return to nature, herbalnatural dyes and natural dyeing have come to the fore. In this context, dyeingapplications with traditional methods and recipes using various herbal dyes are aimed.In this study, applications were made to 100% wool yarns using Daisy (Anthemis chia)and Madder / Root Dye (Rubia tinctorum L.) In herbal dyeing, natural dyeingprocesses and processes are presented.
Keywords: Sosyal ve Beşeri Bilimler; Sanat; Geleneksel Türk El Sanatları; Halı, Kilm ve Eski Kumaş Desenleri; Social Sciences and Humanities; Art; Traditional Turkish Handicrafts; Carpet, Rug and Ancient Cloth Design; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; SANAT; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; ART; Görsel Sanatlar ve Gösteri Sanatları; Müzecilik; Sosyal Bilimler ve Beşeri Bilimler; Visual Arts and Performing Arts; Museology; Social Sciences & Humanities